Evaluation of the effect of Clearview font and retro-reflective sheeting materials on legibility distance - Gowda, Rakshit N. (Kansas State University, 2010)
During the last several decades, the number of drivers and the number of senior citizens driving on U.S highways has increased significantly along with the number of traffic signs. The median age of the drivers has also increased due to the aging population. Traffic signs provide a plethora of necessary information - directions, guidance, warnings, regulations, and recreation. With today's congestion and higher speed, it's very important to recognize the need for brighter and easier to read signs to increase safety among drivers. In the recent years, there has been innovation in the field of traffic engineering, giving rise to numerous innovations in retro-reflective sheeting materials and fonts. It is important to identify the combination of font and retro-reflective sheeting material, which performs best by increasing the legibility distance between the driver and the sign during both day and night time conditions. The objective of the research was to determine the combination of font (among Clearview 5-W, Series E-Modified and Clearview 5-W-R) and retro-reflective sheeting materials (DG3, Type 4 and Type 1) that produces maximum legibility distance. The objective was also to study the safety benefits of the Clearview font. Both field and computer based tests were carried out to find out which combination of font and retro-reflective material produced maximum legibility distance. From field tests it was found that the Clearview 5-W-R font along with Type 1 reflective material produced the maximum legibility distance in day time conditions, whereas Clearview 5-W-R along with Type 4 reflective material produced the maximum legibility distance at night conditions. It was also seen that while the Type 1 sheeting material performed well during day time, it failed to produce good results during night time. In fact it ended up as the worst performing sheeting material during night time. Based on these observations, it is recommended to use the Clearview 5-W-R in combination with Type 4 retro-reflective sheeting as it showed the most consistent performance compared to all other combinations of fonts and DG3 or Type 1 retro-reflective material.
Keywords: Clearview font; Legibility distance; Retro-reflective material; Guide sign legibility; Traffic safety; Series-E font; Engineering, Industrial (0546)